Mixed valence states in (SmxLa1—x)Tr2Al20 (Tr = Ti and Ta) studied using X-ray absorption spectroscopy. (January 2016) - Yamada, Akira; Higashinaka, Ryuji; Fushiya, Kengo; Asano, Takuya; Matsuda, Tatsuma D.; Mizumaki, Masaichiro; Tsutsui, Satoshi; Nitta, Kiyofumi; Ina, Toshiaki; Uruga, Tomoya; Aoki, Yuji
Abstract: X-ray absorption spectra of (Smx La1-x ) Tr 2 Al20 ( Tr = Ti and Ta), which exhibit unusual magnetic-field-insensitive physical properties, have been measured at the Sm L 3 -edge at selected temperatures between 2.5 and 300 K. The spectra show that the Sm ions are in a mixed valence state and that their average valence is approximately +2.85, with almost no significant temperature and x dependences. For SmTi2 Al20, the average valence of the Sm ions does not display any change associated with the magnetic ordering below 6.5 K.